FEATURES OF SCIENTIFIC RESEARCH IN ECONOMY - MELIKH, OLENA; NEMCHENKO, VALERII (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The current situation of the country requires a fundamental scientific approach to solving many economic problems. The implementation of scientific research will find ways out of the crisis, identify promising areas of economic development and its entry into a civilized market environment, assess the possibilities of using foreign experience of economic development to solve the problems of Ukraine's economy. Differences in the classification of sciences determine the specific direction of scientific research. The peculiarity of economic research is that they are complex, i.e. they study social processes in different areas and with different tools. Peculiarities of economic scientific research are also connected with the peculiarities of economic processes themselves, which are the object of scientific research in economics. In economics, the coexistence of contradictory and even mutually exclusive theories is possible. Economic research and results that have long been considered indisputable can be adjusted, supplemented and even refuted over time. Economics, associated with the description of society, is constantly changing views and theoretical approaches to the analysis of social processes. Therefore, the same economic phenomenon, object or process can be described by several theories, and all of them will be new and original. Despite their specific features, economic research has its own subject area, which differs from other areas of scientific knowledge. This area is most clearly defined in the passports of the relevant scientific specialties. The content of a particular economic specialty has a clear distinction with other specialties, which allows to differentiate the research itself. The key to assigning a specific study to a particular specialty is the field of research. A key mistake in understanding the role of economics in solving problems is to give science itself a natural form, i.e. the belief that the presence of complex theoretical constructions (especially in the form of mathematical models) allows them to be effectively implemented in practice. An important result of scientific research in the economy is participation in projects and implementation of scientific developments in the real sector of the economy.
Keywords: research methodology; economic science; specific orientation